Constitutional Identity of the Czech Republic - Petr, Michal (Common Values and Constitutional Identities: Can Separate Gears Be Synchronised?, 2023)
This section focuses on the relationship between national and European Union (EU) laws from the Czech Republic’s perspective. Its aim is not to provide a comparative analysis of these issues but rather to present a specific Czech perspective, with particular emphasis on the concept of Czech constitutional identity. Thus, this chapter is based on the jurisprudence of the Czech Constitutional Court and the corresponding academic discourse. It begins with a discussion of the incorporation of EU Law into the Czech constitutional order, its direct effect, and the limits on the primacy of EU Law. It concludes that while there are no provisions on the effects of EU Law on the Czech constitutional order, the Constitutional Court uses the principles established by EU Law itself. Notably, even though the Constitutional Court is known to be a strong protector of Czech constitutional identity, the primacy of EU Law has never been called into question. The chapter further examines in-depth the concept of transfer of national sovereign powers to the EU and its constitutional consequences, its legal basis and the procedure for it, and, in particular, its limits, including the ultima ratio supervision of the Czech Constitutional Court. Accordingly, the first ever ultra vires ruling, passed by the Czech Constitutional Court, is explained, including its consequences for further practice. Finally, the Chapter focuses on European values, as enshrined in Article 2 of the Treaty on the European Union, and national identity, protected by Article 4 thereof. The Constitutional Court finds these fundamental values compatible in principle, even though in practice, it did not have to resolve any specific problem concerning this issue.Keywords: constitutional identity, primacy, sovereign rights, ultra vires, Treaty of Lisbon